Oral Administration of Prunella vulgaris L Improves the Effect of Taxane on Preventing the Progression of Breast Cancer and Reduces Its Side Effects - Zhao, Jixue; Ji, Degang; Zhai, Xujie; Zhang, Lirong; Luo, Xiao; Fu, Xin (Frontiers in Pharmacology, 2018)
We aimed to explore the efficacy and safety of Prunella vulgaris L (PVL) combined with taxane for treatment of patients with breast cancer (BC). The main ingredients of PVL were analyzed by High-performance liquid chromatography (HPLC). In the experiment, 424 patients with BC were evenly assigned into two groups: experimental group (EG, oral administration of PVL and taxane) and control group (CG, oral administration of placebo and taxane). The primary endpoint was pathologic complete response (pCR), which was evaluated using Miller and Payne system. The secondary endpoints included adverse events (AE) and overall survival (OS), which were evaluated by Common Terminology Criteria for Adverse Event version and Kaplan–Meier curves, respectively. Response Evaluation Criteria in Solid Tumors was used to evaluate the clinical efficacy of PVL. Estrogen receptor (ER) status was also measured. The main side effects were compared between the two groups. The main ingredients of PVL were caffeic acid and rosmarinic acid, which both exert anti-tumor properties. The average follow-up time was 41 months. Eighteen and 31 patients dropped out from EG and CG, respectively. Overall, pCRs were detected in 94 cases (25.1%), comprising 61 cases (31.4%) from EG and 33 cases (18.2%) from CG (P<0.05). PVL treatment improved the pCR rate and OS time compared with those in CG (P<0.05). The 3-year OS rates were 86.5%and 77.2% in patients from EG and CG, respectively (P<0.05). Moreover, ER status was associated with pCR rate and could be an independent prognostic factor in BC. Moreover, treatment with PVL prevented side effects, namely, neutrophil-reduced fever and anemia caused by chemotherapy. Hence, chemotherapy using PVL and taxane could be a safe and effective treatment for patients with BC. PVL may be a potential adjuvant medicine for BC treatment.